The effect of terrorism on stock markets: evidence from the 21st century - Markoulis, Stelios (Terrorism and political violence, 2020)
This paper examines the relationship between terrorist attacks and stock market performance, by employing the “event-study” methodology to examine eleven major terrorist attacks that occurred in the 21st century. Results suggest that earlier events appear to result in higher negative abnormal returns when compared to more recent ones. Where evident, these abnormal returns seem to persist beyond the date of the event, but tend to disappear rather quickly. Some events appear to exhibit a “spill-over” effect influencing international stock markets too. Our most important finding is that recent events do not seem to influence local or international markets, thus suggesting that investors have learnt to better assess terror events and react more calmly to them.